Mechanical Properties of Bamboo Fibre Reinforced Concrete - Hassan, Muhammad Afiq Aiman; Wan Jusoh, Wan Amizah (Progress in Engineering Application and Technology, 2022)
Concrete is one of the most widely used materials in the construction sector since their materials are easily accessible and can fit to any structural shape, however, plain concrete's characteristics are not very durable that cause by its high amount of cracking or pore structure. The objective of this study are to characterise the physical properties of bamboo fibre, to determine the mechanical properties of bamboo fibre reinforced concrete and lastly to determine optimum percentage of bamboo fibre reinforced concrete. Therefore, 0%, 0.5%, 1% and 1.5% of bamboo fibre was uses in this study with 30mm length of bamboo fibre and majority of procedure was followed the British Standard (BS) method. Based on the result obtain, concrete that containing of bamboo fibre cannot significantly improve the slump, concrete density, water absorption, compressive strength, tensile strength, flexural strength and ultrasonic pulse velocity (UPV) and the characteristics of bamboo fibre that absorb more water was affected the slump result and causes of occur honeycomb and 30 N/mm2 concrete strength are not achieved. It means that, result for plain concrete achieved the highest result compared to another sample with mix proportion of bamboo fibre. Therefore, the uses of bamboo fibre in concrete are not suitable since of the characteristics that absorb water and bamboo fibre is commonly used in textile industry and polymer composite product.